Development, architecture and the formation of heritage in late-twentieth century Iran : a vital past - Mozaffari, Ali; Westbrook, Nigel (Manchester University Press, 2020)
What is the relationship between development as a globalizing project and the production of cultural specificities in developmental contexts? Utilising an architectural lens, this book illustrates how development instigates interest in the past and in the process, creates heritage. It show multiple uses of the past and their contestation in highly fluid social contexts.